Effects of high-frequency transcranial magnetic stimulation on functional performance in individuals with incomplete spinal cord injury: Study protocol for a randomized controlled trial - de Araújo, Amanda Vitória Lacerda; Barbosa, Valéria Ribeiro Nogueira; Galdino, Gilma Serra; Fregni, Felipe; Massetti, Thais; Fontes, Sara Lynn; de Oliveira Silva, Danilo [UNESP]; da Silva, Talita Dias; Monteiro, Carlos Bandeira de Mello; Tonks, James; Magalhães, Fernando Henrique (Springer Nature, 2017)
Background: Repetitive transcranial magnetic stimulation (rTMS) has been investigated as a new tool in neurological rehabilitation of individuals with spinal cord injury (SCI). However, due to the inconsistent results regarding the effects of rTMS in people with SCI, a randomized controlled double-blind crossover trial is needed to clarify the clinical utility and to assess the effect size of rTMS intervention in this population. Therefore, this paper describes a study protocol designed to investigate whether the use of rTMS can improve the motor and sensory function, as well as reduce spasticity in patients with incomplete SCI. Methods: A double-blind randomized sham-controlled crossover trial will be performed by enrolling 20 individuals with incomplete SCI. Patients who are at least six months post incomplete SCI (aged 18-60 years) will be recruited through referral by medical practitioners or therapists. Individuals will be randomly assigned to either group 1 or group 2 in a 1:1 ratio, with ten individuals in each group. The rTMS protocol will include ten sessions of high-frequency rTMS (5 Hz) over the bilateral lower-limb motor area positioned at the vertex (Cz). Clinical evaluations will be performed at baseline and after rTMS active and sham. Discussion: rTMS has produced positive results in treating individuals with physical impairments; thus, it might be promising in the SCI population. The results of this study may provide new insights to motor rehabilitation thereby contributing towards the better usage of rTMS in the SCI population. Trial registration: ClinicalTrials.gov, NCT02899637. Registered on 25 August 2016.
Keywords: Incomplete spinal cord injury; Motor rehabilitation; Non-invasive brain stimulation; Plasticity; Repetitive transcranial magnetic stimulation